1979
DOI: 10.1007/bf00113870
|View full text |Cite
|
Sign up to set email alerts
|

Review paper: Heat transfer between liquid helium and solids below 100 mK

Abstract: The many experimental determinations of heat transfer between liquid helium and solids are reviewed and compared with the existing theories. Generally heat transfer is a complex process at low temperatures, involving parallel heat paths with several resistances in series in each path. The standard theories for the individual resistances are reviewed and as far as possible a definite value of the expected resistance obtained. ddute He m hqutd He, metals m liquid He, metals m dtlute He m hquld 4He, and miscellan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

1983
1983
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(8 citation statements)
references
References 118 publications
0
8
0
Order By: Relevance
“…Cooling by demagnetisation often uses elaborate refrigeration stages [74] on state-of-the-art, custom-built dilution refrigerators [73], or vibration isolated systems on commercial, cryogen-free dilution refrigerators [78,79]. While these systems can readily reach bulk electron temperatures ∼ 100 μK , it is not straightforward to use them to cool a nanoelectronic sample to similar temperatures.…”
Section: Cooling Techniquesmentioning
confidence: 99%
See 1 more Smart Citation
“…Cooling by demagnetisation often uses elaborate refrigeration stages [74] on state-of-the-art, custom-built dilution refrigerators [73], or vibration isolated systems on commercial, cryogen-free dilution refrigerators [78,79]. While these systems can readily reach bulk electron temperatures ∼ 100 μK , it is not straightforward to use them to cool a nanoelectronic sample to similar temperatures.…”
Section: Cooling Techniquesmentioning
confidence: 99%
“…10a and b. This cryostat also has the inherent benefit of lower mechanical vibrations because there is no pulse-tube cooler, from which [107] there can be a significant additional heat leak through eddy-current heating [79,88] and additional electrical noise [108]. The particular dilution refrigerator used for the results shown in Fig.…”
Section: Demagnetisation Cooling With Only On-chip Refrigerantmentioning
confidence: 99%
“…The probability for energy exchange by a 3 He quasiparticle can be deduced from the Kapitza thermal boundary resistance [38,39]. In his review Harrison concluded that a lower limit had been reached at RT ∼ 300 K 2 /W for 1 cm 3 of sintered metal powder heat exchanger.…”
Section: Scattering Ofmentioning
confidence: 99%
“…This idea has been realized in Hunklinger et al (1973), Graebner and , Harrison (1979), Hu and Walker (1977), Hunklinger et al (1973), and Hunklinger and Arnold (1976), for example, in various modifications of the dipole echo experimental technique. Consequently many experimental methods that are useful for studying magnetic systems remain relevant for the analysis of TS's in amorphous solids.…”
Section: Interactions Between Tunneling Systems: Spectral Diffusionmentioning
confidence: 99%